1988
DOI: 10.1093/clinchem/34.9.1816
|View full text |Cite
|
Sign up to set email alerts
|

Immunoturbidimetric method for routine determinations of apolipoproteins A-I, A-II, and B in normo- and hyperlipemic sera compared with immunonephelometry.

Abstract: We describe a method for routine immunoturbidimetry of apolipoproteins (apo) A-I, A-II, and B in both normo- and hyperlipemic sera. A special antiserum reagent, consisting of a highly concentrated mixture of nonionic and anionic detergents (final concentration in the assay, 36 g/L), rapidly removes intrinsic turbidities of even strongly lipemic sera without interfering with the antigen-antibody precipitation reaction. The method has good precision, and obviates the need for special sample pretreatment, extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In this method, human apo A‐I binds specifically to a precipitating antibody (sheep anti‐apo A‐I diluted in phosphate buffer stabilized with 0.09% sodium azide), and the turbidity is measured at a wavelength of 340 nm. The absorbance increase is directly proportional to the concentration of apo A‐I 19.…”
Section: Methodsmentioning
confidence: 99%
“…In this method, human apo A‐I binds specifically to a precipitating antibody (sheep anti‐apo A‐I diluted in phosphate buffer stabilized with 0.09% sodium azide), and the turbidity is measured at a wavelength of 340 nm. The absorbance increase is directly proportional to the concentration of apo A‐I 19.…”
Section: Methodsmentioning
confidence: 99%
“…Apo B level was measured in whole plasma, on a Cobas-Bio centrifugal analyzer (Roche Diagnostic) using immunoturbidimetric assays [Rifai and King, 19861. The immunoturbidimetric method has been shown to yield reliable results for routine assays of apo B, not only in normolipemic, but also in hyperlipemic sera [Siedel et al, 1988). The change in turbidity of the sample against a reagent blank was measured at 340 nm after 0.5 and 360 sec of incubation at 37°C.…”
Section: Measurement Of Apomentioning
confidence: 99%
“…There are many studies in the literature which compared the results of different spesific proteins, such as CRP, IgA, IgG, IgM, C3, C4, haptoglobin, transferin, apolipoproteins, RF etc. held by nefelometric and turbidimetric methods, and results of two methods were found to be correlated with each other [21,[28][29][30][31][32]. Correia et al [28] found that CRP levels measured by either methods were correlated with each other, in both unstable angina patients and in patients with non-ST elevation acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 96%